Litter size variation in didelphid marsupials: evidence of phylogenetic constraints and adaptation. (24th November 2018) - Battistella, Thaís; Cerezer, Felipe; Bubadué, Jamile; Melo, Geruza; Graipel, Maurício; Cáceres, Nilton
Abstract: Litter size in mammals can be influenced by morphological and environmental variables. Among mammals, the family Didelphidae includes a diverse group of New World endemic marsupials, with extensive records of variation in litter size across species. The aim of this study was to assess factors that influence litter size variation in didelphid marsupials. Phylogenetic least squares regressions were performed between the response variable, litter size, and a set of predictor variables, i.e. body size, pouch presence and geographical, climatic and productivity variables. The results showed that, despite the high phylogenetic signal, litter size is under the influence of body size and climatic variables, having latitude and elevation as their proxies. Body mass showed a positive linear relationship with litter size, although with a non-significant increasing litter size in smaller, pouchless species. Litter size in the warm, resource-rich tropics tended to be small, but females had several litters per year, increasing fecundity. We argue that offspring survivorship at higher latitudes and in cold climates appears to depend on larger litter sizes in didelphid marsupials, because strong seasonality allows time for only a few or one litter per breeding season.